2017
DOI: 10.1038/nrc.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental regulation of tumour angiogenesis

Abstract: Tumours display considerable variation in the patterning and properties of angiogenic blood vessels, as well as in their responses to anti-angiogenic therapy. Angiogenic programming of neoplastic tissue is a multidimensional process regulated by cancer cells in concert with a variety of tumour-associated stromal cells and their bioactive products, which encompass cytokines and growth factors, the extracellular matrix and secreted microvesicles. In this Review, we discuss the extrinsic regulation of angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
1,189
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,448 publications
(1,209 citation statements)
references
References 224 publications
15
1,189
0
5
Order By: Relevance
“…Physiological angiogenesis is a sequence of cellular events comprising vascular initiation, formation, maturation, remodeling and regression, which are regulated to supply tissue requirements (5)(6)(7). It has been demonstrated that angiogenesis is essential for the growth, metastasis and development of cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…Physiological angiogenesis is a sequence of cellular events comprising vascular initiation, formation, maturation, remodeling and regression, which are regulated to supply tissue requirements (5)(6)(7). It has been demonstrated that angiogenesis is essential for the growth, metastasis and development of cancer (8).…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis is considered a key requirement for cancer growth and progression (109). This is highlighted by the fact that several angiogenesis inhibitors are in clinical trials for cancer treatment (110).…”
Section: Cell-non-autonomous Roles Of Hs Signaling In Cancermentioning
confidence: 99%
“…ECM is characterized by biochemical properties specific for each tissue, and may be involved in overcoming the host’s immune surveillance [18,27,28,29]. …”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…The modulation in the number and/or function of the specific TME cells involved in tumor progression is often associated with a better outcome in cancer therapy, and for this reason, the selective inhibition of the PI3K/mTOR axis correlates not only with the efficacy in leukemias, but also improves the immunotherapy in different solid cancer [27,55]. Recent studies showed that the inhibition of different hub of PI3K/mTOR pathways impacts the different TME components (Table 2).…”
Section: Immunoregulatory Functions Of Mtormentioning
confidence: 99%